Proximal femoral replacement: A salvage treatment of cephalomedullary nails' mechanical failures in the elderly population. Issue 7 (July 2021) - Innocenti, Matteo; Guido, Davide; Cozzi Lepri, Andrea; Maritato, Ernesto; Carulli, Christian; Matassi, Fabrizio; Civinini, Roberto
Highlights: Proximal femur replacement is a potential first line salvage treatment in catastrophic proximal femur nail failure among the elderly population. Immediate weight bearing, low complications' and one-year mortality rates are the most favourable findings reported in our study. Dislocation is the most common complication within the first six months after surgery. Abstract: Background: The use of proximal femoral replacements (PFR) has been recently described for catastrophic internal fixation failures. PFR is an attractive treatment option because it is technically straightforward and allows for immediate mobilization of the patient. The aim of the study was to determine the survivorship, functional outcome and complications' rate in a group of elderly patients who underwent proximal femoral replacement as a salvage treatment after femur cephalomedullary nails' mechanical failures. Methods: We evaluated 21 patients who underwent salvage of a failed cephalomedullary nail by using a single design PFR at our institution between 2014-2017. A cemented stem was used in all cases. Radiographs were assessed for fractures, sign of loosening, presence of heterotopic ossification and leg length discrepancy. Functional evaluation was performed through Harris Hip Score (HHS), FIM™ and Time Up and Go test (TUG). Kaplan-Meier estimator was used to determine the overall implants' survival. Results: The average age at the time of surgery was 83years. The mean follow-up was 3.1years. We recorded 3 dislocations of which 2 required a revision. No case of septic or aseptic failure was reported. Two patients died respectively at 11 and 14 months after surgery. At the last follow-up the mean HHS, FIM™, and the TUG improved significantly (p<0.05). Conclusion: Immediate weight bearing, good functional outcomes, low complications' and one-year mortality rate make the proximal femur replacement with megaprostheses a potential first line treatment of intertrochanteric/subtrochanteric fixations' failures among elderly, osteoporotic, frail patients. Dislocation is the most common complication to bear in mind within the first six months after surgery.